A case-controlled study on AngioJet rheolytic thrombectomy and catheter-directed thrombolysis in the treatment of acute lower extremity deep venous thrombosis. (April 2020) - Zhu, Jun; Ni, Cai-Fang; Dai, Zhen-Yu; Yao, Li-Zheng; Li, Wen-Hui
Objective: This study aims to compare the efficacy and safety of AngioJet rheolytic thrombectomy vs. catheter-directed thrombolysis in patients with acute lower extremity deep vein thrombosis. Methods: Between the period of February 2015 and October 2016, 65 patients with documented acute lower extremity deep vein thrombosis were treated with catheter-directed intervention. These patients were divided into two groups: AngioJet group and catheter-directed thrombolysis group. Comparisons were made with regard to efficacy and safety between these two groups. Results: In the AngioJet group, complete or partial thrombus removal was accomplished in 23 (72%) and 3 (9%) patients, respectively. In the catheter-directed thrombolysis group, complete or partial thrombus removal was accomplished in 27 (82%) patients and 1 (3%) patient, respectively. In the AngioJet group, the perimeter difference between the suffered limb and healthy one declined from 5.1 ± 2.3 cm to 1.4 ± 1.2 cm ( P  <   0.05). In the catheter-directed thrombolysis group, the perimeter difference declined from 4.7 ± 1.6 cm to 1.5 ± 0.9 cm ( P  <   0.05). The mean urokinase dose was 0.264 ± 0.135 million units in the AngioJet group and 1.869 ± 0.528 million units in the catheter-directed thrombolysis group ( P  <   0.05). The duration of thrombolysis was 4.2 ± 1.7 h in the AngioJet group and 73.6 ± 18.3 h in the catheter-directed thrombolysis group ( P  <   0.05). The occurrence of complications in these two groups was 19% and 18%, respectively (not significant). Conclusion: AngioJet rheolytic thrombectomy is a new, safe and effective approach for treating acute lower extremity deep vein thrombosis. When compared to catheter-directed thrombolysis, this treatment provides similar success with lower urokinase dosage and shorter duration of thrombolysis.